Exploring processes of change: A narrative study of the journey from person status to patient status within a mental health low threshold facility - Høgås, Mariell; Josephsson, Staffan; Alsaker, Sissel (Journal of Recovery in Mental Health)

(untitled) (Ontario Shores Centre for Mental Health Sciences, 2025)
Objective: The frequent occurrence of structural changes can be a frustrating experience for everyone involved. The purpose of this study was to explore how service users within a recovery-oriented low threshold mental health service perceive being part of a structural change process within the service, related to documentation of healthcare in a low threshold context. The change that took place changed the service user’s position from person status to patient status. The study is part of a larger research study where part of it is published elsewhere.Methods: Photovoice-workshops led to a photovoice exhibition which forms the basis for further analysis. The data from the workshops was interpreted through narrative analysis based on Polkinghorn, in which possible new stories were created by identifying plots in the material. In narrative methodology, 'plot' refers to actions and events driven by tension, which gain meaning through a story. Three plots regarding service users' experiences of being part of the structural change process were identified.Results: The three plots identified were the plot of unpredictable change, the plot of hope, and the plot of new perspectives. These plots were further written into a coherent narrative, and the results are presented as a new possible story named “A possible story of change.”Conclusion: The findings present a story of how a structural change process appears in the given context and how it is experienced for the service users affected by the changes.Funding: This study was funded by the Norwegian University of Science and Technology, Faculty of Medicine and Health Science, Department of Mental Health.